Influence of Polyvinyl Alcohol Content on Starch-Based Bioplastic Reinforced with Chitosan and Microcrystalline Cellulose - Putra, Bagus Kharisma; Andoko, Andoko; Afandy, Mochamad Viky; Pasha, Muhammad Faizullah; Prasetya, Riduwan (Chimica et Natura Acta, 2026)
Starch-based bioplastics are promising sustainable alternatives to petroleum-based plastics; however, their limited mechanical strength and stability restrict broader packaging applications. This study investigates the influence of polyvinyl alcohol (PVA) content on the structural and functional properties of starch-based bioplastic films reinforced with chitosan and microcrystalline cellulose (MCC). Films prepared by solution casting with varying PVA compositions were characterized in terms of density, mechanical properties, thermal stability, biodegradation behavior, antibacterial activity, and structural features. Increasing PVA content produced denser film structures with improved tensile strength and thermal stability, while elongation at break reached its maximum at the intermediate formulation, indicating a strength–ductility trade-off. The control film exhibited antibacterial inhibition zones of 12.6 mm against Staphylococcus aureus and 8.8 mm against Escherichia coli, with activity decreasing at higher PVA content. These findings demonstrate that adjusting PVA composition effectively tailors the multifunctional performance of starch-based bioplastic films for sustainable packaging applications.